IMPACT OF GST ON THE MANUFACTURING SECTOR IN INDIA - Devarajappa.Sn. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The introduction of the Goods and Services Tax (GST) in India on July 1, 2017, marked a significant milestone in the country’s economic and taxation landscape. Designed as a comprehensive, destination-based tax system, GST aimed to replace the complex web of central and state-level indirect taxes with a unified structure, promoting ease of doing business and creating a common national market. The manufacturing sector, being one of the largest contributors to India’s Gross Domestic Product (GDP) and employment, experienced profound changes under the GST regime. Prior to GST, the manufacturing sector faced numerous inefficiencies arising from cascading taxes, fragmented supply chains, and varying tax rates across states. The burden of multiple levies such as excise duty, VAT, CST, and entry taxes not only increased the cost of production but also complicated compliance processes. GST addressed these challenges by subsuming major indirect taxes and introducing a seamless input tax credit mechanism, which significantly reduced tax cascading and improved cost efficiency for manufacturers. The impact of GST on the manufacturing sector has been multifaceted. On the positive side, it has led to reduced logistics costs, optimized supply chains, and enhanced competitiveness for both domestic and export-oriented manufacturers. The abolition of state border check-posts has improved the speed and predictability of goods movement, while uniform tax rates have simplified pricing and market expansion strategies. However, the sector also faced challenges, particularly during the initial transition period, such as increased compliance requirements, technological adaptation, and temporary disruptions in operations. Overall, GST has catalyzed a shift towards formalization, transparency, and efficiency within the manufacturing sector. While some segments faced short-term difficulties, the long-term implications point towards a more integrated, competitive, and growth-oriented manufacturing ecosystem in India.